Thumb Arthrodesis in The Arthritis Cases: A Scoping Review - Ghifar Akbar; Viskasari Pintoko Kalanjati; Teddy Heri Wardhana (Journal Orthopaedi and Traumatology Surabaya)
Backgrounds: Osteoarthritis in the thumb is a common condition affecting men and women, especially postmenopausal women, causing pain, swelling, and reduced hand function. Arthrodesis is a treatment option for thumb arthritis, increasingly accessible in medical practice, though coverage remains limited. This article aims to review recent case reports on thumb arthrodesis in older people over the last three years, depicting the method's use and outcomes.